2013
DOI: 10.1063/1.4818794
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of efficiency of InGaN-based light emitting diodes through strain and piezoelectric field management

Abstract: We report calculations of the strain dependence of the piezoelectric field within InGaN multi-quantum wells light emitting diodes. Such fields are well known to be a strong limiting factor of the device performance. By taking into account the nonlinear piezoelectric coefficients, which in particular cases predict opposite trends compared to the commonly used linear coefficients, a significant improvement of the spontaneous emission rate can be achieved as a result of a reduction of the internal field. We propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…8) also confirmed the expectations of higher efficiency for tensile strained devices. This was also experimentally observed by Zhang and Tansu, 37 further confirming that the non-linear model of piezoelectricity appears to be not just qualitatively but also quantitatively correct.…”
Section: Iii-n Light Emitting Diodessupporting
confidence: 82%
See 2 more Smart Citations
“…8) also confirmed the expectations of higher efficiency for tensile strained devices. This was also experimentally observed by Zhang and Tansu, 37 further confirming that the non-linear model of piezoelectricity appears to be not just qualitatively but also quantitatively correct.…”
Section: Iii-n Light Emitting Diodessupporting
confidence: 82%
“…Reproduced with permission from Ref [37]. Proposed c-plane InGaN LED device structure using a metamorphic layer before the MQW region which is grown on the top of n-type GaN layer.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…P total is inserted into the Poisson equation to solve for the potential distribution, where ᭞ÁP ¼ q. Note that the second-order piezoelectricity 35,36 was not considered here since for a blue LED this effect will only lead to changes in polarization on the order of 3%-7%, which is in the acceptable range.…”
Section: Methodsmentioning
confidence: 99%
“…112,120,121 The prime requisite for a better understanding of experimental information is probably an improved description of carrier transport across the active region. Promising efforts are represented by momentum-resolved models 23,122 and analytic-band Monte Carlo (MC) transport simulations, 123 but the need for a full-band MC approach (FBMC, possibly integrated with microscopic models of radiative and nonradiative recombination processes) is apparent, especially after the recent debate following the proposed identification of Auger recombination as the dominant mechanism in droop from electron emission spectroscopy experiments, 124 where FBMC analysis has suggested that the LED structure under investigation was probably unsuitable to recover an Auger signature.…”
Section: Discussionmentioning
confidence: 99%